El Niño Argentino de Mauricio Kartun y la producción de sentido político: el teatro como “ladrillazo a la vidriera” - Dubatti, Jorge (Latin American Theatre Review, 2010)
This article proposes that the political thought of Mauricio Kartun is a fundamental key for the analysis of his political theatre. Beginning with the theoretical notions of “concepción de teatro” and “estructura racional,” El Niño Argentino (2006) is analyzed in its relation to socialist thought. The metaphor of El Niño Argentino is referentially sent back to Argentina’s immediate past, to the government of Carlos Menem and the peak of neoliberalism in Argentina of the 90s. Kartun no longer believes in “dramaturgia de la seguridad, de la confianza ciega,” which relied on the discourse of the Socialist Party and on the “soberbia” of a truth that was once believed to be flawless, but rather he continues to reaffirm his socialist conviction, which makes him — in addition to a playwright who participates in the current political movement — an intellectual of Carta Abierta. El Niño Argentino is theatre of “denuncia” (not of “anuncia”), a theatre that unmasks the subjectivity of the Right (rooted in the origins of Argentina, brutal during the years of the dictatorship and during their rise in this last period, since 2001), but that does not offer a solution. This is a theatre of the Left that shows no sign of resignation or despair, and through the act of condemnation, searches with persistent desire, for a new sociability. (JD, Article in Spanish)